OP0127 TRANSCRIPTIONAL ACTIVITY OF SURVIVIN CONTRIBUTES TO MATURATION AND FUNCTION OF THE INTERFERON-GAMMA PRODUCING T CELLS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Erlandsson, M.; Andersson, K. M.; Nair, N.; Damdimopoulos, A.; Töyrä Silfverswärd, S.; Pullerits, R.; Barton, A.; Bokarewa, M. I.
Abstract : Background: Interferon gamma (IFNg) signalling and downstream effects make important contribution in pathogenesis of rheumatoid arthritis (RA). Here, we propose a mechanism by which oncoprotein survivin participates in development of IFN-dependent repertoire of T cells in RA patients. Objectives: We study the role of survivin in the phenotype of CD4 T cells of RA patients. Methods: CD4 cells of RA patients and healthy controls were purified from blood, activated and subjected to RNAseq, ChIPseq with antibodies to survivin (BIRC5) was performed on CD4+ cells. Histone H3 ChIPseq was performed using antibodies to H3K27ac, H3K27me3 and H3K4me3. Statistical analysis was performed In R-studio using the Bioconductor package DESeq2, clustering using Spearman and Ward.D2. Results: Unsupervised clustering of CD4 samples by expression of 48 core Th cell markers identified subsets of CD28 hi CD27 hi IFN neg central memory cells (Tcm), CD28 lo CD27 lo IFN lo effector memory cells (Tem) and CD28 null CD27 null IFN hi terminal effector cells (Tte). Tte cells showed classical features of Th1 cells including high levels of TBX21, TNFa and IL32 and signs of activation in IFN signalling machinery. Interestingly, they combined the features of peripheral Tregs CD25 hi Foxp3 hi IKZF2 neg and IL10 producing cells together with type 1 regulatory cells, which rely on transcription factors BATF and IRF1 for the differentiation and produced high amounts of perforin and granzyme B. Importantly, Tte CD4 cells had also high transcription of BIRC5 (p=1.15e-18). To study if BIRC5 is a part of IFN signalling, CD4 cells were cultured with survivin inhibitor YM155 and activated with IFNg. RNAseq analysis revealed 2033 (FC<2.0, n=336) differentially expressed genes in the IFN stimulated cultures. Interestingly, a substantial number of these IFN-dependent genes was significantly reduced in the survivin-deficient cultures and included among others CD28, FoxP3, IKZF2, ICOS, BATF, PRDM1, CXCR3, IRF4 and IRF8. Analysis of the peak sequences identified enrichment for composite motifs for IRFs (ETS:IRF, p1.0e-124; bZIP:IRF, p=1.0e-640), indicating that survivin is important for IFNg signalling. Numerically, the peaks containing ETS:IRF motifs were most prevalent and identified in total within 49.7% of all survivin-ChIP peaks. Frequent was co-localisation of the IRF:bZIP and IRF:ETS motifs within the survivin peaks. Among the IRF motifs dominated those suitable for IRF1 (p=1, 0e-127) and IRF8 (p=1, 0e-84). However, the DNA binding motifs of these two are alike. Encouraged by the survivin ChIPseq results, we wanted to know its relation to histone marks. We observed that 50% of survivin peaks containing both IRF:bZIP and IRF:ETS motifs are co-localized with the H3K27ac marks. In total, 16 of 48 core Th cell markers used for patients clustering were identified by survivin ChIPseq, co-localized with IRF composite motifs and histone marks. They were also dependent of survivin for expression. Conclusion: his study showed that survivin binds to DNA and regulates the core gene expression contributing to maturation and function of the IFNg producing Th1 cells. References: - Disclosure of Interests: Malin Erlandsson: None declared, Karin ME Andersson: None declared, Nisha Nair: None declared, Anastasius Damdimopoulos: None declared, Sofia Töyrä Silfverswärd: None declared, Rille Pullerits: None declared, Anne Barton Consultant of: AbbVie, Maria I Bokarewa: None declared